Conflicts in the strait of Hormuz: implications towards Oman and Iran - Mohd Ridzuan Md Ariffin; Noraini Zulkifli (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Strait of Hormuz is a vital global oil chokepoint that links the Persian Gulf and the Gulf of Oman to the Indian Ocean and Arabian Sea. It contains narrow international shipping lines in the territorial waters of Iran and Oman, and the narrowest point is only two kilometres wide. Nevertheless, major powers have devoted their interest in the Strait especially the United States of America. This research has been conducted to analyse the factor contributing to the conflict in the Straits of Hormuz and its implications for Iran and Oman. The objectives of this research are: i) to identify the importance of the Strait of Hormuz; ii) to examine the causes and impacts of the conflict in the Strait of Hormuz for Iran and Oman; and iii) to analyse the potential cooperation between Iran and Oman in handling the dispute in the Strait of Hormuz. This research has used qualitative approaches and secondary data were the main sources. The concepts of power and national interest have been used to explain the issues. The findings of this research are i) the strategic location of the Strait of Hormuz has become a factor of conflicts as it is the SLOC to economic activities and strategic purpose; ii) the conflicts in the Straits of Hormuz will cause a decline of economic activities and the Straits to become a battlefield to both countries; and, iii) both countries should use diplomacy to settle their crisis which if escalates, will bring disaster to each side.